Obstetricians and gynecologists' opinions about the Affordable Care Act and their expectations about how it will impact their practice - Anderson, Britta L. (Prev Med Rep, 2016)
As the primary healthcare providers for women, obstetrician-gynecologists' (OB/GYNs) experiences with and opinions about the Affordable Care Act (ACA) are important to understand. An online survey was sent to 1000 randomly selected OB/GYNs who were members of the American College of Obstetricians and Gynecologists (ACOG) in 2014. Of those, 523 opened the email and 163 responded (31% participation rate). Data were collected August 2014-October 2014 and analyzed in 2015–2016. Support for the ACA was widely distributed, with the largest subset of the sample (about 21%) in the “very supportive” category. Opinions of the ACA were more supportive than they were in a previous study conducted in 2011. When given a list of possible positive and negative impacts of the ACA on their practice, roughly 1 in 5 reported that the ACA increased work-related stress (28%), decreased total profits (22%), and lowered career satisfaction (22%), whereas 8.6% reported that the ACA increased quality of care. Around half of the providers thought that their newly insured patients would have the same level of education (42%) and numeric ability (55%) as their current patients. Almost all respondents (87%) indicated that it is at least slightly important for patients to understand their numeric likelihood of risk (such as numeric risk information from medications, treatments, and other procedures you might prescribe) —31% think it is extremely important and 44% think it is moderately important.